REVITALISASI AYAT-AYAT PERDAMAIAN DALAM MEMBENDUNG ARUS SEKTARIANISME - Muh. Khamdan (Farabi, 2017)
This paper proves that religion has been remain as a source of peace and compassion. The conflict that occur it’s influenced by their interpretational politic of textually religious doctrine with no any integration to the social and community context. The strategy to meet peaceful-state conception and religious law committed by Islamic leaders endorsed the archipelago with Pancasila as the state’s foundation. The accomodative constitution it’s basically implemented by the mutual agreement on the same area with no-sectarian action to defending the state with the Medina Charter as well as the first moslem’s communities has been done. The pattern of the radical Islamic movement's understanding of the nature of transnational normally associated with the evidence there is no law except from God and those who use the law apart from God is a kafir. Violence in the name of religion that still bloom occurred in Indonesia indicated that the attitude and behaviour of most community Indonesia no longer in accordance with the principles of Pancasila. Society tends to choose violence or strong penalties in the face of difference. This research use approach to conflict theory and the theory of social identity in analyzing potential deviants in society.